Study on association of iron status in children with simple febrile seizure and without seizures - Gowda B. L., Anantha Narayana; Samuel, Praveen C. (International Journal of Contemporary Pediatrics, 2018)
Background: Considering the age prevalence of iron deficiency anaemia and febrile convulsion which are the same, the role of iron in the metabolism of neurotransmitters (such as GABA and serotonin) and some enzymes (such as monoaminoxidase and aldehideoxidase), the function of hemoglobin in conveying oxygen to the brain and since fever can exacerbate symptoms that result from anaemia, a relationship between iron deficiency anaemia and febrile convulsions is probable. Thus, the present study was conducted to determine the iron profile in children with simple febrile seizures and febrile children without seizures and also to find out the association between iron levels and simple febrile seizures. Methods: A cross sectional comparative study was conducted among the infants and children aged between 6 months to 6 years with complaints of fever with/ without seizures attending Pediatrics OPD, Sri Siddartha Medical College, Tumkur during the period between 2016 to 2018. Purposive sampling of equal number of children in two study groups were made. Demographic data, seizure details, nature of febrile illness, family history of epilepsy /febrile seizures, temperature at admission and nutritional status were recorded. For laboratory assessment, 2 ml venous blood was drawn and sent for estimation of complete blood count with peripheral smear. Statistical analysis was done using SPSS version 16. Results: Among 112 study participants, 60.7% were anaemic. The indicators of iron deficiency anaemia like Hb%, MCH, TIBC and S. ferritin were associated with febrile seizures and were statistically significant. Conclusions: Anaemia prevalence in infants and young children is high and was significantly associated with febrile seizures.